Analyzing Engine Performance and Combustor Performance to Assess Sustainable Aviation Fuel Blends - Ziyu Liu; Xiaoyi Yang (Aerospace, 2024)
FT blends derived from biomass have been confirmed to benefit reductions in GHG and particulate matter (PM). An improvement in combustibility is predicted to reduce fuel consumption and lead to further emission reduction. Various FT fuel blends (7%, 10%, 23%, and 50%) were assessed in terms of their potential for energy savings and emission reduction in a ZF850 jet engine. The engine performance, including the thrust, fuel consumption, emissions, exhaust gas temperature (EGT), acceleration, and deceleration, was investigated in terms of the whole thrust output, while combustor performance parameters, including EIUHC, EIPM2.5, EICO, EINox, and combustion efficiency, were also discussed. The benefit gained in engine performance was nonlinearly related to the blend ratio, which indicated that the available FT blends required appropriate fuel properties coupled with the engine design. According to the superior improvements derived from the 7% FT fuel blend and 23% FT fuel blend, an appropriate lower C/H ratio and higher combustion efficiency with low PM emissions led to a reduction in fuel consumption. Through global sensitivity analysis, changes in the thrust-specific fuel consumption (TSFC) and the thrust and combustion efficiency with various fuel properties were captured. These can be classified as engine-influenced and fuel-influenced (EIFI) parameters. EICO and EINOx are mainly dependent on the combustor and engine design and can be categorized as engine-influenced and fuel-less-influenced parameters (EIFLI), while EIUHC and EIPM2.5 can be categorized as EIFI parameters. The results of this work could extend our understanding of the impact of FT blends on engine performance and GHG reduction.